P–118 A sperm selection technique to mitigate paternal contributions to embryo aneuploidy. (6th August 2021) - Keating, D; Haddad, M; Tavares, D; Rosenwaks, Z; Palermo, G D
Abstract: Study question: Can microfluidic sperm selection (MFSS) select male gametes without sperm chromatin fragmentation (SCF) and double-stranded DNA breaks (dsDNA) in order to generate euploid conceptuses? Summary answer: Couples treated by ICSI with MFSS had significantly improved embryo ploidy rates and pregnancy outcomes, demonstrating the efficacy of this novel selection method. What is known already: SCF has been linked to infertility, specifically to embryo developmental and implantation failure. This damage can be both single-stranded (ssDNA) or double-stranded (dsDNA). Recent studies have shown that dsDNA in particular causes chromosomal aberrations and contributes to embryo aneuploidy, which leads to implantation failure. Study design, size, duration: Consenting couples treated at our center by intracytoplasmic sperm injection (ICSI) with spermatozoa selected by MFSS were included. The majority of these couples had a medical history significant for elevated SCF, recurrent implantation failure, and embryo aneuploidy. ICSI clinical outcome, as well as preimplantation genetic testing for aneuploidy (PGT-A) and frozen embryo transfer (FET), was recorded and compared to the couples' historical treatments following sperm selection by density gradient centrifugation (DGC). Participants/materials, setting, methods: From 2016 to 2020, 51 consenting men had their ejaculates screened for SCF levels by terminal deoxynucleotidyl dUTP transferase nick-end labeling (TUNEL) using a commercially available kit. At least 500 spermatozoa were assessed per patient, with a normal threshold of ≤ 15%. To screen for dsDNA, neutral Comet using a modified in-house protocol was also performed in a pilot study. At least 200 spermatozoa were assessed per patient, with a normal threshold of ≤ 3%. Main results and the role of chance: A total of 51 men (average age, 41.0±8 years) had mean sperm concentrations of 39.0±33x106/mL, 38.4±12% motility, and 2.1±1% normal morphology. Following DGC and MFSS, the concentrations were 4.7±8 and 4.3±8x106/mL and the motility was 64.0±33 and 98.0±3%, respectively (P < 0.0001). The average SCF decreased from 20.1±18% in the ejaculate to 16±3% following DGC, but was 2.9±4% after MFSS. The dsDNA fell from 3.4±3% in raw specimens to 2.9±1% after DGC, and to only 0.5±0.7% following MFSS (P < 0.0001). These men underwent ICSI with their female partners (average age, 37.3±4 years), with sperm selected by DGC; they achieved a fertilization rate of 56.4% (337/597) with 26.0% euploid embryos (36/139). FET cycles from these embryos yielded an implantation rate of 8.3% (2/24) and a clinical pregnancy rate (CPR) of 15.4% (2/13), but both miscarried. These couples then underwent ICSI with MFSS, with a fertilization rate of 78.0% (588/754; P < 0.0001) and 50.0% (172/344; P < 0.0001) euploid embryos after PGT-A. A total of 37 embryos have been replaced, with an implantation rate of 67.6% (25/37; P < 0.0001) and a CPR of 73.5% (25/34; P < 0.001), with an ongoing/delivery rate of 70.6% (24/34; P < 0.0001). Limitations, reasons for caution: While the oocyte contribution cannot be discounted, MFSS was able to yield spermatozoa that had the highest motility and ability to produce euploid embryos following ICSI. Wider implications of the findings: The genome and epigenome of the spermatozoon, and their contribution to reproductive outcomes, are being vigorously explored and scrutinized. Alternative approaches to gamete selection, such as MFSS, in couples with elevated SCF and dsDNA provide the best chances for future pregnancies by mitigating embryo aneuploidy. Trial registration number: Not applicable